Managerial timing and corporate liquidity: - Brockman, Paul; Chung, Dennis Y. (Journal of Financial Economics, 2001)
We investigate the timing of open market share repurchases and the resultant impact on firm liquidity. Using the Stock Exchange of Hong Kong's unique disclosure environment, we identify the exact implementation dates for more than five thousand equity buybacks. We find that managers exhibit substantial timing ability. Consistent with the information-asymmetry hypothesis, bid–ask spreads widen and depths narrow during repurchase periods. We decompose bid–ask spreads and show that adverse selection costs increase substantially as market participants respond to the presence of informed managerial trading. Our findings provide additional insight into how markets process information and have significant implications for corporate payout and disclosure policies.